Punishment and Crime. The Reverse Order of Causality in The White Ribbon Punishment and Crime - Gerwin van der Pol (Journal for Religion, Film and Media, 2018)
This article explores, within a sociological-psychological framework, the problematic moral emotions of spectators evoked by watching the film Das weiße Band (The White Ribbon, Michael Haneke, DE/AT/FR/IT, 2009). As always in Michael Haneke's films the spectator's moral system is severely put to the test, upon watching the unimaginable actions people are capable of. At first sight the shown atrocities that remain unpunished seem to cause the spectator's distress. The real horror, however, lies in the fact the evil occurs within the boundaries of a religious society that hails itself as good and just. The word of God as a moral guide becomes ineffective in this film and in Dogville (Lars von Trier, NL/DK/UK/FR/FI/SE/DE/ IT/NO 2003), a film used as comparison. Both films exemplify that in the end, the most difficult conclusion to process by the spectator is that the worst crime is feeling morally superior and teaching others how to behave. In The White Ribbon this teaching is projected as the punishment that causes the crimes.